2023
DOI: 10.3390/e25091263
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Vital Nodes in Hypergraphs Based on Von Neumann Entropy

Feng Hu,
Kuo Tian,
Zi-Ke Zhang

Abstract: Hypergraphs have become an accurate and natural expression of high-order coupling relationships in complex systems. However, applying high-order information from networks to vital node identification tasks still poses significant challenges. This paper proposes a von Neumann entropy-based hypergraph vital node identification method (HVC) that integrates high-order information as well as its optimized version (semi-SAVC). HVC is based on the high-order line graph structure of hypergraphs and measures changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Up until now, the research works on the chromatic entropy of a hypergraph are found in only one paper: we refer to the reader to [8]. In it, some tight upper and lower bounds of such graph entropy, as well as the corresponding extremal hypergraphs, are obtained.…”
Section: Definition Of Edgementioning
confidence: 99%
See 1 more Smart Citation
“…Up until now, the research works on the chromatic entropy of a hypergraph are found in only one paper: we refer to the reader to [8]. In it, some tight upper and lower bounds of such graph entropy, as well as the corresponding extremal hypergraphs, are obtained.…”
Section: Definition Of Edgementioning
confidence: 99%
“…Shannon entropy is of great importance in the field of graph structure information theory. Based on Shannon entropy and some graph variables, many graph entropies were proposed; we refer to the reader to [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. For graph entropy, there are lots of applications in chemistry, network, biology and so on; we refer to the reader to [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%